KOMUNIKASI PERSUASIF TIM HUNTER TOKOPEDIA DALAM MEREKRUT NEW MERCHANT TOKOPEDIA REGIONAL GROWTH EXPANSION (RGX) PEKANBARU - Chairani Syafira Anthoni; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The development of e-commerce in Indonesia has helped people a lot today, starting from the easier access to transportation, to buying and selling transactions that can be done online. The existing e-commerce, one of which is Tokopedia, is alleged to have more advantages for traders and buyers alike. Persuasive communication is often used by parties who have specific goals, one of which is the Tokopedia Hunter Team in recruiting New Merchants. The task of the Tokopedia RGX Pekanbaru Hunter team is to gather sellers or business people who have not yet joined Tokopedia, in this task the Hunter team plays a very important role as an extension to reach out to sellers throughout the city. This study aims to determine the credibility, persuasive messages and persuasive communication methods carried out by the Tokopedia Pekanbaru RGX Hunter Team in recruiting new Merchants in Pekanbaru. The approach method used in this study is qualitative with descriptive method, namely a method that attempts to describe and interpret objects according to what they are. In this study using a purposive technique with several predetermined informant criteria. The research subjects consisted of Hunter, Merchant and City Partner Performance with data collection techniques in the form of observation, interviews and documentation. The results of the study show that the Tokopedia RGX Pekanbaru Hunter Team has high credibility. This was obtained because the Tokopedia Hunter team has three components that measure credibility, namely trustworthiness, experience and knowledge, and attractiveness. The persuasive communication used by the Tokopedia RGX Hunter Team has proven successful in attracting Merchants to join Tokopedia. This is evidenced by the dozens of Merchants recruited by the Tokopedia RGX Hunter Team. Keywords : Persuasive Communication, Tokopedia, Regional Growth Expansion (Rgx) Pekanbaru